Pengaruh Penerapan Good Corporate Govermance Mengenai Kinerja Keuangan pada Koperasi Pemasaran Trangsan Manunggal Jaya Kabupaten Sukoharjo (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
This study aims to determine the effect of Good Corporate Governance (GCG) guidelines, including transparency, accountability, responsibility, independence, and impartiality, on the financial performance of the Trangsan Manunggal Jaya Marketing Cooperative. Data were collected through questionnaires, observations, and literature reviews from 46 respondents who understood the implementation of GCG in cooperatives. Data analysis was performed using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results showed that transparency, accountability, and responsibility significantly influenced financial performance, while independence and impartiality did not. The regression model was simultaneously significant with an R² value of 0.549, indicating that the independent variables explained 52.8% of the variation in financial performance, with the remainder influenced by factors outside the model.